Morphological characterization of chilli germplasm in Bangladesh - Rahman, S; Hossain, MA; Afroz, R (Bangladesh Journal of Agricultural Research, 2017)
An experiment was conducted using 60 chilli germplasm in the experimental field of Plant Genetic Resources Centre (PGRC), Bangladesh Agricultural Research Institute (BARI), Joydebpur, Gazipur during winter 2013-14 to characterize the germplasm based on morphological traits. Data were recorded as per the descriptor developed by Biovarsity International (BI) and Minimal Descriptor of Agri-Horticultural Crops. The germplasm were collected from different parts of Bangladesh and evaluated for 22 qualitative and 5 quantitative characters. Distinct variation among the germplasm was observed in all the qualitative parameters except cotyledonous leaf shape and fruit persistence. The maximum variation was observed in fruit colour both at mature and immature stage. Fruit colour was observed in four categories, namely green, black, green with blackish blush and dark green. The germplasm AMS-42, AMS-45, RI-35 and AH-5 showed black coloured fruit indicating their high carotenoid content. Leaf pigmentation was found in AMS-39, AMS-44, AMS-45, AH-1and RI-2 germplasm. Purple coloured corolla observed in AMS-42, AMS-45, AH-1 and AH-2 showing their high pollen fertility. The highest quantitative variation was observed in yield per plant suggesting that the evaluated germplasm could be used in developing high yielding variety. Considering the yield and yield contributing parameters the germplasm AI-1, AI-2 and RI-2 were found better among the 60 germplasm. Bangladesh J. Agril. Res. 42(2): 207-219, June 2017